The Arrest of Mantis Shrimp (Harpiosquilla raphidea) Margin and Marketing Efficiency in Kampung Nelayan - Firmansyah, Firmansyah; Tampubolon, Nancy Angeline; Darmawi, Darlim; Hariski, M.; Ramadan, Fauzan (Agrikan Jurnal Agribisnis Perikanan, 2021)
This research was conducted in Kampung Nelayan Village, Tungkal Ilir Sub-district for mantis shrimp marketing institutions from April to June 21021. The purpose of this study was to analyze margins and marketing efficiency of mantis shrimp catches in Kampung Nelayan Village. The data collected in the form of primary data and secondary data with survey methods is then analyzed descriptively with quantitative methods. The results showed that there are 2 marketing channels for mantis shrimp in Kampung Nelayan Village, namely marketing channel I from fishermen to intermediary traders and then to agent traders. From fishermen to agent traders. Marketing channel I total margin of Rp. 35.796/head and marketing efficiency of 8,59% (inefficient). Marketing channel II total margin Rp. 32.088/head and marketing efficiency of 9,34% (inefficient).